Emotion, Law, and the Novel - Bertrand, Denis (Semiotika, 2025)
“From emotion to law”, or “From emotional discourse to legal discourse”, the semiotic approach, enriched by its theory of passions, allows us to trace the path that leads from one to the other. Against the backdrop of the current ecological crisis, I first analyse the gradual transformation of the passionate and militant discourse of anger (Greta Thunberg) into an institutionalised discourse, the ultimate form of which is achieved in the legal document (the Paris Climate Agreement, 2015). In a second part, I extend the discussion to a more global reflection on genericity, and I examine, both in terms of enunciative expression and the formal codification of content, the conditions and issues at stake in the transition from passionate, “clutching” and subjective discourse to the “declutching”, objective discourse of law: the instability of the collective, the status of simulacra, the elaboration of enunciative praxis, the syntax of the norm. Through the central motif of the court case, widely the novel depicts this transformative dynamic and the intertwining of the emotional and the legal. I will conclude by illustrating this with the example of the trial at the end of Zola’s La Bête humaine. Literature, and particularly novels, depict this transformative dynamic and the intertwining of the emotional and the legal through a powerful motif: the trial. I conclude by illustrating this with the example of the trial at the end of Zola’s La Bête humaine.